Comparison of Surgical Outcome between Endoscopic and Microscopic Type 1 Tympanoplasty - Mahmud, Md Khalid; Alam, Md Monjurul; Islam, Md Mainul; Rahman, Mohammad Habibur; Majumder, Riashat Azim; Akhtar, Nasima; Datta, Pran Gopal; Naha, Abirvab (Bangladesh Journal of Otorhinolaryngology, 2020)
Background: Chronic otitis media (COM) is the long-standing infection of a part or whole of middle ear cleft characterized by ear discharge & perforation. The most common presenting symptoms are ear discharge, mild to severe hearing loss, sometimes tinnitus even vertigo. Treatment of COM is mainly operative. The treatment of inactive mucosal variety of COM is Type 1 tympanoplasty. It can be done by microscopic or endoscopic technique. Both methods have some merits and demerits. Objectives: Aim of the study was to compare the surgical outcomes between endoscopic and microscopic type 1 tympanoplasty. Methods: This study was carried out in the Department of Otolaryngology–Head & Neck surgery of Bangabandhu Sheikh Mujib Medical University, Dhaka from March 2017 to June 2019 and 60 (30 in each group) patient were included in the study. All patients underwent type 1 tympanoplasty. In Group A endoscopic tympanoplasty cases and in Group B microscopic tympanoplasty cases were placed. Operation duration, post-operative pain, postoperative hearing status, graft uptake was compared in two groups. Results: There were no significant difference of graft uptake and hearing gain (>0.05). But endoscopic operative time and post-operative pain were less than microscopic group (<0.05). Conclusion: Through endoscopic tympanoplasty is a newer approach and it has some limitations. As endoscopic tympanoplasty requires less time, less pain with similar graft uptake and audiological success. It can be adopted as an alternative method of tympanoplasty. Bangladesh J Otorhinolaryngol; October 2020; 26(2): 109-115